2020
DOI: 10.36560/131220201258
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity and effects of combined agrochemical in Scaptotrigona bipunctata bees

Abstract: The commercial insecticide Fastac Duo is a combined insecticide, widely used in different crops, acting on insects, affecting both pests and pollinators, such as bees. In this study, the effects of sublethal concentrations of Fastac Duo in stingless bees Scaptotrigona bipunctata were evaluated. Worker forager bees were exposed to the insecticide and histochemical and morphological analyses were conducted after 24, 48 and 72 h of ingestion. Brain analysis of S. bipunctata revealed changes in the chromatin conde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
2
9
0
Order By: Relevance
“…Similar effects were identified by Diniz et al (2020) after oral contamination of Scaptotrigona bipunctata bees with a combined insecticide containing the neonicotinoid and pyrethroid chemical groups. In this study, several morphological Research, Society and Development, v. 10, n. 2, e14310212109, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i2.12109 changes were observed in the midgut, such as the degradation of the peritrophic membrane, epithelium disorganization and the musculature loosening.…”
Section: Midgut Morphological Alterationssupporting
confidence: 60%
“…Similar effects were identified by Diniz et al (2020) after oral contamination of Scaptotrigona bipunctata bees with a combined insecticide containing the neonicotinoid and pyrethroid chemical groups. In this study, several morphological Research, Society and Development, v. 10, n. 2, e14310212109, 2021 (CC BY 4.0) | ISSN 2525-3409 | DOI: http://dx.doi.org/10.33448/rsd-v10i2.12109 changes were observed in the midgut, such as the degradation of the peritrophic membrane, epithelium disorganization and the musculature loosening.…”
Section: Midgut Morphological Alterationssupporting
confidence: 60%
“…In contrast, severe histological alterations in the midgut tissues of worker bees in the flagyl group were observed. Among the most noticeable changes was the partial rupture in columnar cells, which may contribute to the rapture of the peritrophic membrane that acts as a food envelope and protective barrier against various physical, chemical, and microbial food components (Terra, 1996;Diniz et al, 2020). In addition, Spread of cytoplasmic vacuoles in epithelium columnar and separation of muscle layer.…”
Section: Discussionmentioning
confidence: 99%
“…In a study conducted by Diniz et al (2020b) the estimated LC50 for Scaptotrigona bipunctata bees orally contaminated with the insecticide Fastac Duo were 0.07 g a.i. L -1 to 24 hours, 0.10 g a.i.…”
Section: Discussionmentioning
confidence: 99%
“…Oral contamination of insects at sublethal doses of agrochemicals can harm their organs (Catae et al, 2014;Diniz et al, 2020b). Catae et al (2014) investigated the effects of the neonicotinoid thiamethoxam on the midgut and Malpighi tubule of A. mellifera and the results indicated that the insecticide is cytotoxic to bees.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation